2002
DOI: 10.1051/0004-6361:20021462
|View full text |Cite
|
Sign up to set email alerts
|

HST images of B2 radio galaxies: A link between circum-nuclear dust and radio properties?

Abstract: Abstract. Almost 60% of the B2 low luminosity radio galaxies have been observed with the Hubble Space Telescope. We present an analysis of the dust features, which are often present in the form of circum-nuclear disks or lanes, and show that there are correlations between radio source and dust properties. It is found that nearby radio sources in which a jet has been detected tend to have dust more often than sources without jets; the dust is often in the form of disks or lanes. Moreover the radio jets are clos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 21 publications
7
50
0
Order By: Relevance
“…Our classification of dust structures is consistent with results from de Ruiter et al (2002). The 11 sources with H i absorption all have dust, and are split between extended dust (5) and disks (6).…”
Section: Dust Morphologysupporting
confidence: 87%
See 1 more Smart Citation
“…Our classification of dust structures is consistent with results from de Ruiter et al (2002). The 11 sources with H i absorption all have dust, and are split between extended dust (5) and disks (6).…”
Section: Dust Morphologysupporting
confidence: 87%
“…In contrast, the optical nuclei of FR I radio galaxies appear unobscured (e.g. de Koff et al 1996;Chiaberge et al 1999;Capetti et al 2002), though the host galaxies often have kiloparsec-scale dust rings and lanes (de Koff et al 2000;Verdoes-Kleijn et al 2002;de Ruiter et al 2002). Chiaberge et al (1999) found that the brightness of the optical core correlates with the brightness of the radio core.…”
Section: Introductionmentioning
confidence: 99%
“…1). Using HST data, de Ruiter et al (2002) derive a typical gas column density of 2.7 × 10 20 cm −2 for the gas clouds seen in NGC 315, a value very similar to that found in our radio observations for the H i in emission. We obtain the same column density for the narrow absorption if we assume T spin = 100 K. This could further support the idea that the gas is at larger radius since such value for T spin is characteristic for the ISM not affected by the active nucleus.…”
Section: The Narrow Hi Absorptionsupporting
confidence: 84%
“…Extended reservoirs of diffuse atomic gas are not unusual in early-type galaxies (Oosterloo et al 2007). Dust lanes in radio galaxies are often perpendicular to the jet (de Koff et al 2000), and have masses that depend on jet power (de Ruiter et al 2002), suggesting that the ISM "knows about the jet".…”
Section: Jet-disk Symbiosismentioning
confidence: 99%